ANALISIS KEBUTUHAN SDM KEARSIPAN DI PUSKESMAS LENDANG NANGKA DI ERA DIGITAL - Heni Widhi Amelya; Muhammad Aditya Rachman (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2026)
Puskesmas Lendang Nangka has transitioned to a digital system using the e-Puskesmas application to manage archives, replacing the previous manual system. This research aims to analyze the human resource needs for managing archives in the digital era. The method used is descriptive qualitative with data collection through interviews and observations. The results show that the medical record system and outgoing letters (such as Health/Sick Certificates, Birth Certificates, etc.) are already integrated in e-Puskesmas, but there is still a shortage of specialized staff. Currently, only 4 medical officers also handle archives. This system is less effective for long-term digital data management. The research suggests adding archivist staff or administrative heads who understand digital technology to ensure data security and quality of health administration services.